A new analog of dihydroxybenzoic acid from Saccharopolyspora sp. KR21-0001 - Janthanom, Rattiya; Kikuchi, Yuta; Kanto, Hiroki; Hirose, Tomoyasu; Tahara, Arisu; Ishii, Takahiro; Thamchaipenet, Arinthip; Inahashi, Yuki (Beilstein Journal of Organic Chemistry, 2024)
Actinomycetes are well-known as the main producers of bioactive compounds such as antibiotics, anticancers, and immunosuppressants. Screening of natural products from actinomycetes has been an essential part of several drug discovery programs. Finding such novel biologically active metabolites is immensely important because of their beneficial health effects. Recently, the discovery of new compounds has diverted attention to rare actinomycetes, since they are rich sources of natural products. In this study, a collection of rare actinomycetes at Kitasato University has been screened for potential novel compound producers. Among the rare actinomycetes, Saccharopolyspora sp. KR21-0001 isolated from soil on Ōha Island, Okinawa, Japan was selected as a potential producer. The strain was cultured in 20 L of production medium in a jar fermenter and the culture broth was extracted. Further purification revealed the presence of a new compound designated KR21-0001A (1). The structure was elucidated by NMR, and the absolute stereochemistry was determined by advanced Marfey’s method. The results indicated that 1 is a new analog of dihydroxybenzoic acid. 1 has no antimicrobial activity against bacteria and fungi but showed potent antioxidant activity.
Keywords: antioxidant activity; dihydroxybenzoic acid analog; rare actinomycetes